Experimental-modelling geochemical study of potential CCS caprocks in brine and CO2-saturated brine. (January 2016) - Szabó, Zs.; Hellevang, H.; Király, Cs.; Sendula, E.; Kónya, P.; Falus, Gy.; Török, Sz.; Szabó, Cs.
Highlights: We present geochemical behaviour of potential CCS caprocks from the Pannonian Basin. The experimental and kinetic geochemical modelling results are in partial agreement. Reference model simulations for reservoir conditions (lower T) have been performed. For the effect of CO2 faster dissolution and reformation of carbonates is observed. Boehmite and smectite formation is also expected with CO2 in the system. Abstract: The work presented in this paper is a part of the evaluation of the saline aquifers of the Pannonian Basin for CO2 geological storage in Hungary. The presented results evaluate the long-term caprock behaviour for the effect of a possible CO2 injection and are relevant in case of other similar storage complexes as well. Three potential core samples were selected, crushed and their one-two month long laboratory batch experiments were carried out in CO2 -free and CO2 environments. Solution composition of the reacted brine and mineral composition of the reacted rock samples were analyzed. Furthermore, kinetic geochemical modelling was carried out in PHREEQC to better understand the observed changes during experiment. Reference model simulations for reservoir conditions (lower T) have been also performed. In the rocks, dissolution of the carbonate minerals was observed and also model indications were found for feldspar dissolution, which processes lead to secondary carbonate and clay mineral formation. The effect of CO2 is primarily to increase dissolution rates of the mineral transformation reactions. Boehmite and smectite formation can also be expected among which smectite is considered highly advantageous.